Design of Heat Pump Water Heater (HPWH) System on Km. Meratus Karimata - Andriyan, Andriyan; Prayogi, Urip; Dwisetiono, Dwisetiono (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
The need for hot water on a ship is one of the facilities that must be obtained by the crew while carrying out their duties on the KM. Meratus Karimata is one of the ships that provide hot water as a facility for crew members. The heating system on this ship still uses the EHHW (Electric Heating Hot Water) heating system which will then be changed to the HPWH (Heat Pump Water Heater) system. This hot water need is based on the MLC (Marine Labor Convention) regarding the provision of recreational facilities on deck accommodation. The provision of hot water needs to be calculated and designed. The first thing to do is to calculate all distribution support components. Then the data for the needs of pumps with a power of 0.504 Kw, valves, shower taps, sink taps, pipe connections, and SCH 40 pipes with a diameter of ¾ "and 1" are obtained. After that, the design is carried out using software assistance. After the design is carried out, the calculation of component costs is carried out with details of the valve price of IDR 10,129,000, pipe IDR 5,186,000, pipe connection IDR 1,751,000, supply pump IDR 1,150,000, HPWH 95,300,000. The price of EHHW and HPWH is a difference of IDR 21,300,000, which is more expensive for HPWH. However, in the calculation of fuel consumption, HPWH is more efficient with HPWH fuel consumption data of 0.11 liters/hour at a cost of Rp.1,249 / hour, while fuel consumption for EHHW is 0.77 liters/hour at a cost of Rp.10,116/ hour.